Pleiotropic effects of simvastatin in physically trained ovariectomized rats. - Bernardes, N. (2013)
This study tested the hypothesis that simvastatin treatment can improve cardiovascular and autonomic functions and membrane lipoperoxidation, with an increased effect when applied to physically trained ovariectomized rats. Ovariectomized rats were divided into sedentary, sedentary+simvastatin and trained+simvastatin groups (n = 8 each). Exercise training was performed on a treadmill for 8 weeks and simvastatin (5 mg/kg) was administered in the last 2 weeks. Blood pressure (BP) was recorded in conscious animals. Baroreflex sensitivity was evaluated by the tachycardic and bradycardic responses to BP changes. Cardiac vagal and sympathetic effects were determined using methylatropine and propranolol. Oxidative stress was evaluated based on heart and liver lipoperoxidation using the chemiluminescence method. The simvastatin-treated groups presented reduced body weight and mean BP (trained+simvastatin = 99 ± 2 and sedentary+simvastatin = 107 ± 2 mmHg) compared to the sedentary group (122 ± 1 mmHg). Furthermore, the trained group showed lower BP and heart rate compared to the other groups. Tachycardic and bradycardic responses were enhanced in both simvastatin-treated groups. The vagal effect was increased in the trained+simvastatin group and the sympathetic effect was decreased in the sedentary+simvastatin group. Hepatic lipoperoxidation was reduced in sedentary+simvastatin (≈21%) and trained+simvastatin groups (≈57%) compared to the sedentary group. Correlation analysis involving all animals demonstrated that cardiac lipoperoxidation was negatively related to the vagal effect (r = -0.7) and positively correlated to the sympathetic effect (r = 0.7). In conclusion, improvement in cardiovascular and autonomic functions associated with a reduction of lipoperoxidation with simvastatin treatment was increased in trained ovariectomized rats.